Validitas Alat Ukur Zarit Burden Interview (ZBI) Menggunakan Model Rasch pada Populasi Indonesia - Agatha Maria Febriani Larantukan; Ananta Yudiarso (Humanitas (Jurnal Psikologi), 2025)
The role of a caregiver often demands significant sacrifices in terms of time, thought, emotions, and energy, leading to various physical and psychological issues. Therefore, a valid and reliable measurement tool is needed to accurately assess caregiver burden. The Zarit Burden Interview (ZBI) is one such tool that is frequently used and has been shown to be valid and reliable in various countries and ethnic groups. However, in Southeast Asia, particularly in Indonesia, there has been limited research on the reliability of the ZBI. This study aims to evaluate the validity of the ZBI within the cultural context of Indonesia using Rasch Model analysis. The study involved 305 caregivers selected through convenience sampling, with the ZBI consisting of 22 items. The analysis showed a Cronbach's alpha value of 0.93, indicating high reliability. The Wright Map indicated a moderate level of item difficulty. Bias was found in item 21 based on gender, items 6 and 8 based on age, items 7, 11, and 12 based on caregiving duration, and items 6, 7, and 18 based on geographic location. Overall, the Indonesian version of the ZBI was shown to be valid and reliable in measuring caregiver burden.The role of a caregiver often demands significant sacrifices in terms of time, thought, emotions, and energy, leading to various physical and psychological issues. Therefore, a valid and reliable measurement tool is needed to accurately assess caregiver burden. The Zarit Burden Interview (ZBI) is one such tool that is frequently used and has been shown to be valid and reliable in various countries and ethnic groups. However, in Southeast Asia, particularly in Indonesia, there has been limited research on the reliability of the ZBI. This study aims to evaluate the validity of the ZBI within the cultural context of Indonesia using Rasch Model analysis. The study involved 305 caregivers selected through convenience sampling, with the ZBI consisting of 22 items. The analysis showed a Cronbach's alpha value of 0.93, indicating high reliability. The Wright Map indicated a moderate level of item difficulty. Bias was found in item 21 based on gender, items 6 and 8 based on age, items 7, 11, and 12 based on caregiving duration, and items 6, 7, and 18 based on geographic location. Overall, the Indonesian version of the ZBI was shown to be valid and reliable in measuring caregiver burden.